Non Immersive Virtual Laboratory Applied to Robotics Arms - Bastidas, Daniela (2022)
This article presents a non immersive virtual laboratory to emulate the behavior of Mitsubishi Melfa RV 2SDB robotic arm, allowing students and users to acquire skills and experience related to real robot, augmenting the access and learning of robotics in Universidad de las Fuerzas Armadas (ESPE). It was developed using the mathematical model of the robotic arm, thus defining the parameters for the virtual recreation. The environment, interaction and behavior of robotic arm was developed in a graphic engine (Unity3D) to emulate learning tasks such in a robotics’s laboratory. In the virtual system, 4 inputs were development for the movement of the robot arm, further to program the robot a user interface was created where the user selects the trajectory such as point to point, line, arc or circle. Finally the hypothesis of the industrial robotic learning process is validated through the level of knowledge acquired after using the system.